Design and tolerance analysis of a large-diameter diffractive telescope. Issue 10 (7th June 2022) - Zhong, Yue; Chang, Jun; Chen, Weilin; Du, Shan; Ji, Zhongye; Jiang, Huilin; Sui, Jie
Abstract : The large-diameter diffractive telescope has the advantage of observing space debris. Some of the key issues are the design and tolerance analysis of the telescope with the segmented primary lens. In this paper, we design a space large-diameter sub-aperture stitching diffractive telescope that can achieve a large diameter of 1438 mm, a long focal length of 2000 mm, and a full field of view (FOV) of 0.34°. Considering the manufacturing and stitching errors of the sub-aperture can affect the telescope's image quality, we provide a tolerance analysis method based on Monte Carlo analysis, which makes the consequence of the tolerance analysis nearly reality. The tolerance ranges are proposed not only for the segmented primary lens but also for the whole telescope system.